Application of 2D fluorescence correlation method to investigate the dilution-induced heterogeneous distribution of the bound FMN in azoreductase - Feng, Juan; Han, Ting; Zhang, Mi-Qing; Zhou, Yu; Wu, Qing-Qin (Chinese chemical letters, 2015)
AzoR is a homodimeric,flavin mononucleotide（FMN）-containing,NADH-dependent azoreductase from Escherichia coli.In this paper,we investigated the effect of the concentration of both AzoR and R59 G on the spectral behavior of the bound FMN using two-dimensional fluorescence correlation spectra.Two cross peaks（530,490） and（580,530） were observed from the dilution-induced 2D asynchronous correlation map of wt AzoR,while only one cross peak appeared at（600,530） for R59 C mutant.This result indicated that the mutation at site 59 influenced the formation of dilution-induced intermediates.The specific activity of both AzoR and R59 G mutant was unaffected by dilution when the enzyme concentration is below 1 μmol/L,which suggested that no significant dissociation of FMN occurred at low concentrations.Additionally,in order to explore the origin of these intermediates,we carried out a2 D correlation analysis using excitation wavelength-dependent fluorescence emission spectroscopy.The results showed that there coexisted two types of FMN that emitted fluorescence at 530 nm and 500 nm,respectively.Taken together,these results suggested that the 2D method is a very powerful method to identify the heterogeneous distribution of the bound FMN in solution.